Effects of closure of an urban level I trauma centre on adjacent hospitals and local injury mortality: a retrospective, observational study. Issue 5 (10th May 2016) - Crandall, Marie; Sharp, Douglas; Wei, Xiong; Nathens, Avery; Hsia, Renee Y
Abstract : Objective: To determine the association of the Martin Luther King Jr Hospital (MLK) closure on the distribution of admissions on adjacent trauma centres, and injury mortality rates in these centres and within the county. Design: Observational, retrospective study. Setting: Non-public patient-level data from the state of California were obtained for all trauma patients from 1999 to 2009. Geospatial analysis was used to visualise the redistribution of trauma patients to other hospitals after MLK closed. Variance of observed to expected injury mortality using multivariate logistic regression was estimated for the study period. Participants: A total of 37 131 trauma patients were admitted to the five major south Los Angeles trauma centres from the MLK service area between 1999 and 2009. Main outcome measures: (1) Number and type of trauma admissions to trauma centres in closest proximity to MLK; (2) inhospital injury mortality of trauma patients after the trauma centre closure. Results: During and after the MLK closure, trauma admissions increased at three of the four nearby hospitals, particularly admissions for gunshot wounds (GSWs). This redistribution of patient load was accompanied by a dramatic change in the payer mix for surrounding hospitals; one hospital's share of uninsured more than tripled from 12.9% in 1999 to 44.6% by 2009. Overall trauma mortality did not significantly change, but GSW mortality steadily and significantly increased after the closure from 5.0% in 2007 to 7.5% in 2009. Conclusions: Though local hospitals experienced a dramatic increase in trauma patient volume, overall mortality for trauma patients did not significantly change after MLK closed.